PENGARUH INDEPENDENSI DAN KOMPETENSI AUDITOR INTERNAL TERHADAP KUALITAS AUDIT DENGAN SELF EFFICACY SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Inspektorat Provinsi Jawa Tengah dan Inspektorat Kabu - Ria Ervina (AKT 15 UMY 411, 2015)
*411 The purpose of this study are to analyze the influence of independence and competence on internal audit quality with self efficacy as variabel moderation in Inspectorate Central of Java and Inspectorate district of Semarang. Variable in this research are the independent variabel as independence (X1) and competence (X2), and dependent variabel is quality of the audit (Y), the research also use variable self efficacy (X3) as variable moderation. The population of this study is audiors on inspectorate in central java and inspectorate district of semarang. Sampling method uses the method purposive sampling , from 38 the auditors. Types of data on this research is primary data, and the method of sampling in a survey by spreading questionnaire to respondents. The research data obtained by distributing 60 questionnaires, and questionnaires that can be used as many as 38. In this research using analysis of multiple regression with software spss 15.0 version. The result of the research indicated that independence of and competence have significant influence on the quality of audit. Self efficacy can strengthen the influence of independence of on the quality of audit , and self efficacy can strengthen the influence of competence on the quality of audit.